(untitled) (Ius Novum, 2021)
An entrepreneur’s secret is one of the grounds on which access to public information can be refused. Administrative courts’ case law stipulates that two elements jointly constitute an entrepreneur’s secret: a tangible one, e.g. a detailed description of the method of service provision, its price and technical conditions of an undertaking, and a formal one, i.e. the will to make some information data secret.